2003
DOI: 10.1097/01.mol.0000073507.41685.9b
|View full text |Cite
|
Sign up to set email alerts
|

Fast flip-flop of cholesterol and fatty acids in membranes: implications for membrane transport proteins

Abstract: Knowledge of these properties provides a framework for understanding transport and metabolism of cholesterol and fatty acids and how their putative membrane and intracellular transporters might function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Serum typically contains external lipids in two forms: non-esterified free fatty acids (FFAs) associated with albumin, and lipoproteins that carry triglycerides, cholesterol and phospholipids encapsulated by apoproteins [8, 9]. Cells can take up FFAs via physical diffusion across the cellular membrane [10] or via active transport aided by membrane-associated protein CD36 or FATPs [11]. Lipoprotein uptake occurs through binding to cell surface receptors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Serum typically contains external lipids in two forms: non-esterified free fatty acids (FFAs) associated with albumin, and lipoproteins that carry triglycerides, cholesterol and phospholipids encapsulated by apoproteins [8, 9]. Cells can take up FFAs via physical diffusion across the cellular membrane [10] or via active transport aided by membrane-associated protein CD36 or FATPs [11]. Lipoprotein uptake occurs through binding to cell surface receptors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, it has been often suggested that cholesterol flip-flop, i.e., the rapid exchange of cholesterol between the two leaflets, can significantly contribute to domain registration (Hamilton, 2003). The proposed mechanism would result primarily from the fact that cholesterol can move significantly faster in the disordered phase in comparison to the ordered one (Risselada and Marrink, 2008).…”
Section: Cholesterolmentioning
confidence: 99%